The Swedish monetary system from a balance sheet perspective - Dirk Ehnts; Jussi Ora (Levy Economics Institute of Bard College, 2024)
In this paper, we discuss the balance sheet mechanics of the Swedish government. We examine spending, government bond purchases, and tax payments. As long as the Swedish central bank, which is created through Swedish laws, supports the Swedish central government, it cannot run out of money. The Swedish government therefore plays a large role in the Swedish economy. It can and should target full employment and price stability, bringing to bear its fiscal power.
Keywords: E62; B52; E12; 330; Riksbank; Swedish crowns; public finance; money creation